2019
DOI: 10.1071/an16391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycerin supplementation on the expression of antioxidant and mitochondrial genes in broilers

Abstract: Crude glycerin has been used as an alternative energy source in animal feeding and can thus change both the animal’s performance and the levels of gene expression related to energy production process and the antioxidant system, since the effect of glycerin depends on its degree of purity in the diet. The aim of this study was to evaluate the effect of crude glycerin inclusion (0, 6 and 12%) in the diet has on performance characteristics and mRNA abundance of genes associated with the mitochondrial function (un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…28 In this study, the activity of GSH-Px and SOD enzymes was increased in the OSO-treated lactating rats. This result is similar to that reported by Araújo et al, 29 who found that both GSH-Px and SOD could promote the decomposition of H 2 O 2 . Overall, we speculated that the increased of GSH-Px and SOD is likely to be an adaptive response to oxidative stress.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 92%
“…28 In this study, the activity of GSH-Px and SOD enzymes was increased in the OSO-treated lactating rats. This result is similar to that reported by Araújo et al, 29 who found that both GSH-Px and SOD could promote the decomposition of H 2 O 2 . Overall, we speculated that the increased of GSH-Px and SOD is likely to be an adaptive response to oxidative stress.…”
Section: Wileyonlinelibrarycom/jsfasupporting
confidence: 92%